Perencanaan Sistem Sanitasi di Daerah Permukiman Padat Penduduk Di Kecamatan Jatinegara, Jakarta Timur - Nur Alifiani Ramadhanty; Pramiati Purwaningrum; Sheilla Megagupita Putri Marendra (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Indonesia is committed to achieving Sustainable Development Goals (SDGs) number 6 by 2030, improving. Kampung Melayu, located in the Jatinegara sub-district, was chosen for sanitation planning due to its limited access to toilets, reaching only 79.21%, far below the set target. The high population density poses challenges in sanitation infrastructure development, exacerbated by limited available and. The planning aims to enhance wastewater sanitation and community well-being. Data collection employed both qualitative and quantitative methods, involving collaboration with the local community and questionnaire distribution. In RW 03, Kampung Melayu, permanent houses lack septic tank facilities. The chosen wastewater treatment system is a communal septic tank, utilizing separate tanks for blackwater and greywater. The plan includes installing 10 septic tank units to serve 100 households. Following the implementation of the plan, there is a remarkable 34,09% increase in the provision of sanitation facilities and infrastructure in Kampung Melayu.